Aktualisasi Diri dan Nilai Pendidikan dalam Novel Bocah Penghalau Kera Karya Sintha Rosse Kamlet - Charoline Vinche (Universitas Indraprasta PGRI, 2022)
This study aims to analyze self-actualization and educational values contained in Sintha Rosse Kamlet Bocah Penghalau Kera novel based on Abraham Maslow's humanistic psychology. The research method used was descriptive qualitative method and content analysis technique. The results showed: 1) Self-actualization was found to be more dominant in this novel as much as 60% % while the value of education was 40%. Eight groups of characters who show self-actualization are found entirely in this novel. The most dominant self-actualization, namely. From the self-actualization data found in the novel Bocah Penghalau Kera, there are 8 groups of self-actualization, starting with the most frequently occurring ones: (1) independence-independence 25 quotes (23.81%), (2) peak experience 18 quotes (17.14 %), (3) focused on democratic issues 16 quotes (15.24%), (4) creativity-appreciation 15 quotes (14.29%), (5) interpersonal relations-acceptance 11 quotes (10.48%), (6) social reality-awareness 10 quotes (9.52%), (7) spontaneity-sense of humor 6 quotes (5.71%), (8) needing solitude 4 quotes (3.81 %). The most common educational value found was the value of divinity education, which was 36 quotes (51.43%), followed by the value of moral education as many as 12 quotes (17.14%), the value of aesthetic education as many as 10 quotes (14.29%), the value of social education is 8 citations (11.43%), and the value of cultural education is 4 citations (5.71%). In this novel, the author provides an example of making life more meaningful through self-actualization of the protagonist, maximizing all his efforts, developing his talents and potentials, never giving up on achieving his goals and achieving the desired success. The author also conveys good values so that readers can wisely take lessons that are expected to be applied in everyday life. Keywords: Self-actualization, educational value, pshycology, character, novel Bocah Penghalau Kera.